Employee participation in organizational change: A case of Tesco PLC - Awadari, Adam Cassia; Kanwal, Shamsa (Goodwood Publishing, 2019)
Purpose: The research work attempts to identify some of the challenges and difficulties that were associated with the recent technological changes in Tesco PLC (from cashier to customer self-checkout) and its related effect on employee attitude and performance. Research methodology: The research is a case study type; a convenient sampling method was used for selecting the sample for the study. The sample chosen for this research comprises of 3 store managers and 13 checkout staff of Tesco Express Kilburn branch. Results: The findings revealed that management and customer assistants were well educated and well aware of the on-going strategic changes by management. Management was also aware of the vital role effective communication plays in the overall success of the program but communication had not been very impressive during the initial stages. It was also revealed that customer assistants developed a negative attitude, due to the fear of job insecurity, they had the impression the self-checkout was being implemented to replace their roles. Limitations: A generalization of the phenomenon across the organization's portfolio cannot be drawn on grounds of sample size representation. It is also acknowledged that using only one retail store for the research was a significant limitation covering more stores would have added considerable information to the findings. Contribution: This study has contribution for the formulation of policies and programs that should consider the inclusion of employees as major stakeholders in the design and planning of any organizational change. Keywords: Change management, Employee, Participation, Attitude, Performance